Management of the production of the papaya crop (Cariac, papaya L.) in the colombian lower tropics - Martínez Quintero, Efraín; Universidad Pedagógica y Tecnológica de Colombia; Puentes Montañez, Gloria Acened; Universidad Pedagógica y Tecnológica de Colombia; Medina Castañeda, Nancy Aidé; Universidad Nacional de Colombia (UPTC Editorial, 2023)
This book shows how to produce and manage papaya cultivation in the Colombian lower tropics region, the activities are presented in a sequential manner, both cultural and economic practices that are necessary to obtain sufficient production and achieve profitability cultivation of papaya Carica Papaya in this region, especially in the departments of Meta and Casanare. In this way, the reader finds the stages of crop production in a practical and simple way, illustrating and proposing a methodology from an administrative approach, thus obtaining a didactic text at the beginning of the production period, with planning tools, budget, guides in fertilization, irrigation, integrated pest and disease management, and postharvest programs.